Expression of aromatase in tumor related stroma is associated with human bladder cancer progression. Issue 3 (4th March 2018) - Wu, Shulin; Ye, Jianheng; Wang, Zongwei; Lin, Sharron X.; Lu, Min; Liang, Yingke; Zhu, Xuejin; Olumi, Aria F.; Zhong, Wei-de; Wu, Chin-Lee
ABSTRACT: Putative gender differences in bladder cancer (BCa) have been proposed to result from sex hormone influence. Aromatase is the key enzyme catalyzing the conversion of androgens to estrogens which may result in an intratumoral microenviroment with increased estrogen production. In this study, we investigated the expression pattern of aromatase and its association with BCa progression. Tissue samples from 88 BCa patients who underwent cystectomy were obtained. Using immunohistochemistry (IHC), expression of aromatase in tumor epithelium (TE) and tumor related stroma (TS) were evaluated separately, and the association of aromatase expression status with pathologic variables and overall survival (OS) outcome was examined. High aromatase expression was found in 33/88 (37.5%) of TE and in 65/88 (73.9%) of TS. Increased aromatase expression in TE had a trend to correlate with male gender. Increased aromatase in TS was significantly associated with adverse pathologic variables including higher pathologic pT, positive lymph node metastasis (pN), lymphovascular invasion (LVI), and distant metastasis. In univariate analysis, high aromatase expression in TS was significantly associated with poorer overall survival ( p = 0.014), but this association was not significant ( p = 0.163) in multivariate cox analysis adjusted for independent factors including age at surgery and pN. These results demonstrate that aromatase expression in TS but not TE may play a critical role in BCa progression. Our findings provide direct evidence of aromatase involvement in BCa and suggest endocrine therapy may have a potential role in the treatment of BCa.